SISTEM PENGANGKUTAN SAMPAH DI TPA BUKIT PINANG KOTA SAMARINDA DENGAN HAULED CONTAINER SYSTEM - Agustina, Fitriyati; Yatnikasari, Santi; Zulkarnain, Isnaini; pitoyo, Pitoyo; Asnan, Muhammad Noor (Rang Teknik Journal, 2020)
Garbage collecting and transporting operations are complex and complicated, high traffic congestion and distant mileage cause the transport of waste to become obstructed. The purpose of this research is to know the number of waste time and estimate the need of garbage transport until 2028 in Samarinda. In this study used the time series method with hauled container system as a reference in formulate problems in the garbage transport system. Sampling at the research in the garbage disposal in Samarinda Ulu district of Samarinda city. The data used is population data, area density, number of heads of family, travel time of garbage transportation, mileage, growth rate in each sub-district in Samarinda. The district with many inhabitants is the district of Samarinda Ulu 143,908 inhabitants, 28,781 family head and the closest area of Bukit Pinang landfill with a mileage of about 3.2 km. The need for garbage transport vehicles from 2019 to 2028 is increasing due to the development of population in Samarinda. The analysis gained the need for the city of Samarinda in 2028 a number of 65 and the need for Samarinda Ulu Sub-district as the point of research, 16 cargo/day Truck required 4 units with estimated Timmoon garbage 508,948 m3/day with a distance 3.2 km. Keywords:Garbage, garbage transport, garbage transportation, garbage carrying system